The French aire in Jane Eyre - Emily Eells (Cahiers Victoriens et Edouardiens)
This article examines how Brontë makes French into a kind of licence for freedom of speech issued to both the eponymous heroine of the novel and the novelist herself. Jane’s knowledge of French qualifies her for the post of governess to Parisian born Adèle, and thus offers her an income and some independence. Significantly, the first French verb Jane learns is être, as if the foreign language were offering her a new life. At Thornfield, she finds herself in a small community of French speaking women. Adèle’s frivolity and clothes-consciousness typify French stereotypes which contrast with Jane’s earnestness and self-government. Rochester calls on his command of French in an attempt to define his non-conventional relationship with Jane. Thanks to the French language, Brontë’s heroine succeeds in constructing her own space in the Victorian domestic world.